EFECTS OF LOCAL OWN-SOURCE REVENUE (PAD) AND CAPITAL EXPENDITURE ON REGIONAL ECONOMIC GROWTH - Chintya Prabawati; Maria Goretti Kentris Indarti (Universitas KH. Abdul Chalim Mojokerto, 2026)
This research examined the direct and indirect effects of local own-source revenue (PAD) and capital expenditure on regional economic growth, with regional financial performance serving as a mediating variable in the former Pati Residency area of Central Java. This research analyzed two decades of panel data (2005–2024) from five regencies. The researchers applied path analysis using a random-effects model and test mediation with the Sobel test. The results reveal that PAD positively affects regional financial performance, whereas capital expenditure does not. The findings also indicate that PAD, capital expenditure, and regional financial performance do not affect regional economic growth. In addition, regional financial performance does not mediate the effects of PAD and capital expenditure on economic growth. These results imply that increasing regional fiscal capacity does not automatically drive real economic growth; therefore, policymakers need a more integrated approach that aligns budget planning with economic development strategies based on local leading sectors. Keywords : PAD, capital expenditure, financial performance, regional economic growth, mediating variable